N-(4-Chlorophenyl)ethanimidamide - Boechat, N.; Kover, W.B.; Ferreira, S.B.; Wardell, S.M.S.V.; Wardell, J.L.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
A twisted conformation is found in the title compound, C(8)H(9)ClN(2), with the ethanimidamide residue being twisted substantially to the benzene ring [dihedral angle = 66.54 (14)degrees]. The conformation about the C=N double bond [1.299 (3) angstrom] is Z. A two-dimensional array with a zigzag topology is formed in the crystal structure via N-H center dot center dot center dot N and N-H center dot center dot center dot Cl hydrogen-bonding interactions.